POTENTIAL COMBINATION OF VIRGIN COCONUT OIL (VCO) AND AZADIRACHTA INDICA EXTRACT FOR ACNE CONTROL: A COMPOSITION PHYTOCHEMICAL AND IN VIVO ANTIBACTERIAL EVALUATION - karta, i wayan; Burhannuddin, Burhannuddin (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Background: Treatment of acne can be done with topical and systematic therapy. There is the bacterial resistance to drugs, so other alternatives are needed that can utilize natural ingredients so that side effects can be reduced. Aims: The objective of this study was to determine the phytochemical content of a blend of VCO and Intaran (Azadirachta indica) leaf extract (VCO-I) at concentrations of 5%, 10%, and 20%, and to assess its effect on the in vivo inflammation induced by P. acnes. Methode: This study has a posttest-only control group design and is experimental. Rats in the experimental group were smeared with VCO-I at concentrations of 0% (P0), 5% (P1), 10% (P2), and 20% (P3); clindamycin (Cindala®) was used as the positive control (K+); and distilled water was used as the negative control (K-). The results: The results showed that VCO-I contained flavonoids, tannins, and alkaloids. The level increases as the mixture's concentration increases. Each VCO-I treatment was able to treat wounds or lesions that appeared due to the induction of P.Acne bacteria. There are differences in each treatment for healing the lesions. Based on the Post Hoc Bonferroni test P2 and P3 were not significantly different from K+, and K0 was significantly different from P0.. Conclusion: The addition of the extract can increase the activity of speeding up the healing of lesions and the effective mixture is at P2 and P3.